Effectiveness of Telemedicine in Reducing Maternal Mortality Rates in Underserved Regions of Indonesia in 2024 - Hartanto, Amelia (Magenta Journal De Healthymedi, 2024)
Maternal mortality remains a critical issue in underserved regions of Indonesia, where access to healthcare is limited due to geographical and socioeconomic barriers. This study aims to evaluate the effectiveness of telemedicine in reducing maternal mortality rates in these regions. A quantitative approach was employed, using pre- and post-intervention data collected from 500 pregnant women and healthcare providers across rural Indonesia. The findings demonstrate a significant reduction in maternal mortality rates from 35.2 to 22.1 deaths per 100,000 live births (p = 0.005), along with improvements in healthcare access, consultation frequency, and hospital visits. Furthermore, telemedicine usage increased from 30% to 85% (p = 0.000), indicating widespread acceptance of remote consultations. While some challenges, such as technical issues and lack of personal interaction, were noted, the overall impact of telemedicine was positive. The results suggest that telemedicine interventions are a promising strategy to reduce maternal mortality in low-resource settings and highlight the need for enhanced infrastructure and user training to maximize its benefits.